Food Security Program: Reducing Food Waste and Improving Food Access for Vulnerable Communities in Medan City - Fahrica, Fharcha; Muhammad, Aditya; Siregar, Putra Apriadi; Larasati, Siti Suci; Suraya, Rani; Moon, Lisa (Universitas Islam Negeri Sumatera Utara, 2025)
The Aksata Pangan program aims to reduce food waste by rescuing surplus food from restaurants, hotels, and bakeries that is still safe for consumption, and then distributing it to vulnerable communities in Medan City, such as orphanages and community centers. The program involves collaboration with the private sector and promotes public awareness of the importance of reducing food waste. During implementation, more than 500 kilograms of food were saved and distributed, providing direct benefits to over 10 orphanages and community centers. A social impact evaluation was conducted through observations, interviews, and questionnaires, which showed that the program succeeded in increasing access to food for people in need and raising awareness about more efficient food management. The results of this program indicate that collaboration between the private sector and non-profit organizations has great potential to reduce food waste and improve social welfare. This program is also expected to serve as a model for sustainable, community-based food management in other regions.